2005
DOI: 10.1111/j.1360-0443.2005.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled screening trial of tiagabine, sertraline and donepezil as cocaine dependence treatments

Abstract: The present findings suggest that tiagabine may be worthy of further study as a cocaine dependence treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…The National Institute on Drug Abuse (NIDA) has developed and implemented a series of treatment trials to evaluate a number of pharmacologic agents as potential treatments for cocaine dependence (Liederman et al, 2000(Liederman et al, , 2005Berger et al, 2005;Ciraulo et al, 2005;Elkashef et al, 2005;Winhusen et al, 2005). Boston University School of Medicine was the site of three NIDA-sponsored cocaine dependence treatment trials that were similar in design.…”
Section: Methodsmentioning
confidence: 99%
“…The National Institute on Drug Abuse (NIDA) has developed and implemented a series of treatment trials to evaluate a number of pharmacologic agents as potential treatments for cocaine dependence (Liederman et al, 2000(Liederman et al, , 2005Berger et al, 2005;Ciraulo et al, 2005;Elkashef et al, 2005;Winhusen et al, 2005). Boston University School of Medicine was the site of three NIDA-sponsored cocaine dependence treatment trials that were similar in design.…”
Section: Methodsmentioning
confidence: 99%
“…De la Garza et al (2008) have also recently reported that the AChE inhibitor, rivastigmine, decreased methamphetamine-induced craving during selfadministration in human volunteers. On the other hand, a preliminary study using donepezil, another cholinesterase inhibitor, did not attenuate cocaine use in a treatmentseeking population (Winhusen et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…Some of the most common cholinergic agonists are cholinesterase inhibitors, and donepezil, galantamine, and rivastigmine are presently available for use in humans (Cummings, 2000;Ellis, 2005). In a preliminary trial of donepezil using the Cocaine Rapid Efficacy and Safety Trial (CREST) study design, however, dozepezil did not produce significant changes in cocaine use (Winhusen et al, 2005). Treatment trials of rivastigmine in the treatment of cocaine addiction are ongoing.…”
Section: Summary and Future Directions For Clinical Researchmentioning
confidence: 99%